(untitled) (Global Journal of Science Frontier Research, 2014)
New Hydrazonic Schiff base was synthesized by reaction Nicotinic hydrazidewith Biphenyl-4,4′- Dicarbal-dehydehave been characterized by elemental analyses IR, massand1H-NMR spectral data Hydrazoic Schiff base have been studied by liquid-liquid extraction towards the metal ion Uo(II) from aqueous phase to organic phase. behave as a good extractant ligand for uranyl ions Uo(II) from aqueous solution, and the study of conditions of extraction shows that the optimum pH values for extraction was (pH= 5.2), so the suitable concentration of Uo(II) ions in aqueous solution which is giving highest distribution ratio (D) was (1×10-4M), in addition the optimum shaking time to reach the equilibria was (60 min.), as well as the stoichiometric study by using three methods shows the structure of Uo(II) ions complex with ligand was 1 : 1 (metal : ligand), in addition the study of organic solvent effect appear there is no straight line relation between the distribution ratio for extraction of Uo(II) ions and dielectric constant for organic solvents but this study demonstrate there is an effect for the structure of organic solvent used, thermodynamic study shows the complexation reaction an endothermic.The new Schiff Bases was studied for antibacterial activities against (Bacillus subtilis and Staphylococcus aureus) are Gram positive and (Salmonella typhi and Escherichia coli) are Gram negative. The compound ligand was exhibited a variable activity of inhibition on the growth of the bacteria.